ANALISIS SISTEM PENERIMAAN PAJAK KENDARAAN BERMOTOR DI UPTD SAMSAT MANADO - Umboh, Wanda Regina; Tinangon, Jantje J; Afandi, Dhullo (Universitas Sam Ratulangi, 2020)
One source of regional income is drived from motor vehicle tax (PKB). Motor vehicle tax that is handed over to the regions which is regulated through Government Regulation concerning regional taxes and the One Roof Single Administrative System (SAMSAT) as an administrative system that is designed to facilitate and accelerate the service of the public interest. The purpose of this study is to analyze the adequacy of the system of moto vehicle tax receipts UPTD SAMSAT Manado. The type of research used is qualitative research only present the data as it is but also attempts to interpret correction as an exixsting factor that includes the viewpoint or process that continues. The result of the study show that internal control system, has been running well and effectively. In the future the UPTD SAMSAT Manado can make other alternatives in PKB payment.